Activation of autophagic pathways is related to growth inhibition and senescence in cutaneous squamous cell carcinoma. Issue 10 (October 2014) - Choi, So Ra; Chung, Bo Young; Kim, Seong Who; Kim, Chang Deok; Yun, Woo Jin; Lee, Mi Woo; Choi, Jee Ho; Chang, Sung Eun
Abstract Cutaneous squamous cell carcinoma (SCC) is a very common resectable cancer; however, cutaneous SCC is highly resistant to chemotherapy if metastasis develops. Activating transcription factor 3 (ATF3) has been suggested as a marker of advanced or metastatic cutaneous SCC. Autophagy is one of the most important mechanisms in cancer biology and commonly induced by in vitro serum starvation. To investigate the role of autophagy activation in cutaneous SCC, we activated autophagic pathways by serum starvation in SCC13 and ATF3‐overexpressing SCC13 (ATF3‐SCC13) cell lines. ATF3‐SCC13 cells demonstrated high proliferative capacity and low p53 and autophagy levels in comparison with control SCC13 cells under basal conditions. Intriguingly, autophagic stimulation via serum starvation resulted in growth inhibition and senescence in both cells, while ATF3‐SCC13 cells further demonstrated growth inhibition and senescence. Apoptosis was not significantly induced by autophagy activation. Taken together, autophagy activation may be a promising antitumor approach for advanced cutaneous SCC.